Creativity and youth entrepreneurial intention: a conceptual model - Dali, Fadli; Hashim, Hasnizawati; A. Halid@Khalid, Rozieana; Abd Kadir, Nor Aziah (UiTM Cawangan Johor, 2021)
The main objective of this paper is to propose a new conceptual model on entrepreneurship in which creativity plays an important role to stimulate entrepreneurial intention (El). The variable of creativity serves as a new and an additional predictor for the entrepreneurial intention in the Theory of Planned Behaviour (TPB) which is a well-blown estimation model for measuring the effect of intention on human behaviour, particularly in the field of entrepreneurship. This study proposed a variable, creativity, as a new predictor of entrepreneurial intention in relation with all other existing variables such as attitude, social norm, and perceived behaviour control. Exploring the role of creativity in TPB could provide new insight into factors stimulating entrepreneurial intention and entrepreneurial behaviour among youths, particularly in rural areas. Besides that, this move will also assist the public authorities in the formulation of extensive entrepreneurial policy-making to help those who would want to get involved in entrepreneurial activity. Hence, this will help society to empower positive entrepreneurial behaviour among youths, particularly in rural areas who face various environmental obstacles but are rich in prospects.